Long-Term Exposure to American and European Movies and Television Series Facilitates Caucasian Face Perception in Young Chinese Watchers. (October 2016) - Wang, Yamin; Zhou, Lu
Most young Chinese people now learn about Caucasian individuals via media, especially American and European movies and television series (AEMT). The current study aimed to explore whether long-term exposure to AEMT facilitates Caucasian face perception in young Chinese watchers. Before the experiment, we created Chinese, Caucasian, and generic average faces (generic average face was created from both Chinese and Caucasian faces) and tested participants' ability to identify them. In the experiment, we asked AEMT watchers and Chinese movie and television series (CMT) watchers to complete a facial norm detection task. This task was developed recently to detect norms used in facial perception. The results indicated that AEMT watchers coded Caucasian faces relative to a Caucasian face norm better than they did to a generic face norm, whereas no such difference was found among CMT watchers. All watchers coded Chinese faces by referencing a Chinese norm better than they did relative to a generic norm. The results suggested that long-term exposure to AEMT has the same effect as daily other-race face contact in shaping facial perception.